Postinfectious COVID-19 Catatonia: A Report of Two Cases - Torrico, Tyler; Kiong, Timothy; D'Assumpcao, Carlos; Aisueni, Uyi; Jaber, Fouad; Sabetian, Katayoun; Molla, Mohammed; Kuran, Rasha; Heidari, Arash (Frontiers in Psychiatry, 2021)
Neuropsychiatric symptoms are a common complication of COVID-19, with symptoms documented both during acute COVID-19 infection (parainfectious) and persisting or developing after the resolution of respiratory symptoms (postinfectious). Patients have presented with a variety of symptoms such as anosmia, thrombotic events, seizures, cognitive and attention deficits, new-onset anxiety, depression, psychosis, and rarely catatonia. Etiology appears to be related to disruption of regular neurotransmission and hypoxic injury secondary to systemic inflammation and cytokine storm. Although rare, catatonia and each of its subtypes have now been reported as complications of COVID-19 and therefore should be considered known to occur in both the parainfectious and postinfectious states. Diagnosis of catatonia in the context of COVID-19 should be considered when work-up for more common medical causes of encephalopathy are negative, there is no identifiable psychiatric etiology for catatonia, and there is a positive response to benzodiazepines.